Effects of autochthonous bacteria and prebiotic supplementation on the growth and survival of Clarias batrachus - T. Rahman (Journal of Agriculture, Food and Environment, 2020)
Studies were conducted to identify the autochthonous bacteria from the intestines of walking catfish, Clarias batrachus,and to evaluate the efficacy of the gut microbessupplementation on the growth and survival of the catfish under laboratory condition. Autochthonous bacteria were isolated from the intestines of experimental fish using Nutrient agar (NA) and de Man, Rogosa, and Sharpe (MRS)agarin duplicate. Primarily,16 gut bacteria were isolated and three isolates were selected viz., Lactobacillussp., Bacillussp., andLactococcus sp. after the phenotypic study. For biosafety evaluation of the selected bacteria, healthy C. batrachusfingerlings (average weight: 10.4± 0.8 g) were challenged with these bacteria at a dose of 107CFU/mL by immersion technique for 7 days. Gut microbiotasupplemented diets were prepared and analyzed for their proximate composition. A 3-week long feeding trial was conducted with ten 35 L capacity rectangular glass aquaria to evaluate the growth performance and survival of 96 C. batrachus fingerlings (average weight: 9.28 ± 1.5 g)fed with the above three gut microbiota supplemented diet and gut microbiota + prebiotic (molasses, yeast, and rice bran) supplemented diet. Morphometric measurements of the experimental fish and water quality parameters were determined weekly. The bio-safety evaluation revealed that the isolates were safe for C. batrachuswith no clinical signs or mortalities during the challenge test. The study revealed better growth and survival of C. batrachuswith gut bacteria supplemented diets but showed much better performance in the cases of all growth parameters while prebiotic was additionally supplemented. Thus, the above mentioned autochthonous gut probiotics and prebiotics could be recommended as an effective eco-friendly health management approach in C. batrachusculture. Further detail study is necessary to establish the fact.